Interleukin 17A Promotes Hepatocellular Carcinoma Metastasis via NF-kB Induced Matrix Metalloproteinases 2 and 9 Expression - Li, Jian (Public Library of Science, 2011)
BACKGROUND:  IL-17A is a pro-inflammatory cytokine that plays important role in inflammatory disease pathology and tumor microenvironment. The aim of this study is to investigate the effect of IL-17A on the progression of hepatocellular carcinoma (HCC). METHODOLOGY AND PRINCIPAL FINDING: Expression pattern of IL-17A in clinical HCC samples (n = 43) was determined by immunohistochemistry staining. Transcript levels of MMP2, MMP9 and IL-17A were measured in another 50 pairs (including tumor and related non-tumor tissues) HCC samples. Cell growth, focus formation, cell migration, invasion and western blot assays were used to characterize the functional and signaling mechanisms in IL-17A-treated HCC. Association study was used to identify clinical significance of IL-17A in HCC. Compared with paired non-tumor tissue, higher frequency of IL-17A-positive cells was detected in tumor tissues in HCCs with metastasis, and the frequency of IL-17A-positive cells was also significantly associated with poor prognosis of HCC (P = 0.01). Functional study found that IL-17A could promote HCC cell migration and invasion. Further molecular analysis also showed that IL-17A could upregulate MMP2 and MMP9 expression via NF-κB signaling activation. CONCLUSIONS:  IL-17A could promote HCC metastasis by the upregulation of MMP2 and MMP9 expression via activating NF-κB signaling pathway.